PENGARUH ORIENTASI PASAR, ORIENTASI KEWIRAUSAHAAN DAN KEMAMPUAN PEMASARAN, TERHADAP KINERJA BISNIS UMKM CLOTHING LINE - Sindy Purnamasari; Andreas Wijaya (Universitas Bunda Mulia, 2020)
One of driven national economy in Indonesian had been provided from the Micro, Small and Medium Enterprises (MSMEs), They play essential role both in national trade and labour force, According to survey data from the Central Statistics (BPS) MSMEs contributed 7,38% to national economy in 2016, In addition, fashion industry rose gradually 8,7% compared in last year with the amount of export finished 13.29 billion in 2017. Moreover, MSMEs absorb around 97% of the national workforce, while Large Enterprises only absorb around 3% of the total national workforce and Indonesian MSME businesses that are urgently needed by Micro Enterprises. This depencency encourage the competition indirectly, as a result businesses in the fashion need to consider market orientation to find opportunity, innovativey through entrepreneurial orientation, and marketing capabilities to maintain their business. This reseearch was conducted to investigate the effect of market orientation, enterpenuership orientation, market capabilities on the performance of MSME businesses. The research method used is an associative method, with primary and secondary data types as a reference. Respondents collected in this study were 150 respondents, with closed questionnaire containing 15 question attributes. In essence, the present studies found market orientation, entrepreneurship orientation were not significant, this result may not hold support business performance. On the other hand, market orientation, entrepreneurship orientation had significant outcomes and indicates both of market and enterprenuership orientation can drivers the using of marketing capabilities. Similar results, marketing capabilities had significant effect to business performance. However, like any empirical research , this study has limitations, Based on this research, firstly the results have only been tested in one industry, additionally the role of internet had change trend of market orientation, market capabilities. This findings can be hint to another researcher to explore in technology as third party in case of sharing economy